PENGARUH HEDONIC SHOPPING MOTIVATIONS DAN STORE ATTRIBUTES TERHADAP SHOPPER LOYALTY - Siti Fathonah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The aim of this study is to investigate the influence of the hedonic shopping motivations and store attributes on the shopper loyalty. Considering the results of previous studies, this study also investigates the role of consumers’ demographic in moderating the process of shopper loyalty formation. Samples of 200 respondents who shopped in Solo Square were involved in the study. Structural Equaion Modelling was employed to analyze the research model. The results indicate that the store attributes does not only affect the shopper loyalty directly, but also influences indirectly through hedonic shopping motivations. Meanwhile, the role of respondents’ demographic varies in moderating the formation of shopper loyalty.Keywords: Hedonic shopping motivations, Store attributes, Shopper loyalty, Age, Gendcer, Income.